THE SYSTEM OF COMPLEX REHABILITATION OF CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER: NOVEL APPROACH TOWARDS OBSERVATION AND TREATMENT - O. R. Nogovitsina; E. V. Levitina ("Paediatrician" Publishers LLC, 2012)
Study objectives: novel approaches to complex rehabilitation system organization of children with attention deficit hyperactivity disorder(ADHD) and efficacy analysis of the present system. A system of rehabilitation scrutinized in the article consists of three levels: familyschool/ kindergarten - medical institution. While designing a novel approach towards rehabilitation 150 teachers that work with ADHD children had their psychoemotional status checked. Analysis of the efficacy of complex rehabilitation of 100 ADHD children during 4 years and 50 ADHD children that refused being followed up was carried out. Primary critera of efficacy were as follows: decrease of carelessness, hyperactivity, impulsivity, determined by the questionnaire score, amelioration of cognitive function and of behaviour. Psychological escort of the teachers was designed on the basis of their psychoemotional characteristics. Reasonability and social importance of the complex rehabilitation system for ADHD children. Implication of the novel approach of system organization allows to maintain constant rehabilitation of such children in every society.